Modelling of caving and deformation mechanisms of the hangingwall of the Printzsköld oreboby at Malmberget mine - Umar, Sraj Banda; Sjöberg, Jonny; Savilahti, Thomas (Journal of the Southern African Institute of Mining and Metallurgy, 2017)
Sublevel caving in Malmberget mine results in mining-induced surfacedeformation. One of the currently mined orebodies is the Printzsköldorebody. As mining deepens there is need to assess the behaviour of thecave formed in the subsurface above this orebody. Numerical analysis wasused to assess the effects of extraction to deeper levels and performstrength parametric studies. Stress redistribution was studied, and theresults showed high stress buildups in the hangingwall and the crownpillar. Two failure mechanisms have been identified – shear and tensile.Reducing cohesion by 50% increased the area of the yielded zone by morethan 100% in the hangingwall. Validerad;2017;Nivå 2;2017-06-13 (andbra)